The Risk of Electronic Audit and its Impact on The Quality Audit (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The auditing profession faces a challenge referred to as information technology ,Information technology has set the profession of auditing in constant challenge because it has made the world an open - limited system through communication technology .The importance of this research stems from the need to identify the nature of the  risks of electronic auditing  after turned  from manual checking to electronic auditing due to developments in technologies  in all sectors.  The risk of electronic auditing  the risk of information technology infrastructure and the risks of applications and other  related to communication processes, several conclusions have been reached, implementation of programs with goods specifications in the electronic auditing  process will lead to safety of work and  reduce the risk of electronic auditing . The research highlights these  risks and their impact on the quality of auditing .